2018
DOI: 10.1192/bjo.2018.16
|View full text |Cite
|
Sign up to set email alerts
|

A population study of Norwegian psychiatric patients referred for clinical brain scanning

Abstract: BackgroundPatients with psychiatric conditions are often referred for a brain scan during the course of their diagnostic workup.AimsThe aim of our study is to determine frequency and type of organic brain pathology, the relationship to age, gender and psychiatric diagnosis.MethodWe investigated magnetic resonance imaging and computed tomography brain scans from consecutively referred patients over a 10-year period (January 2002-December 2011). The reasons for referral, estimated psychiatric diagnosis, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In this report among the most commonly observed abnormalities were vascular lesions and infarcts, localised (e.g., hippocampal) or general atrophy, benign structurers (e.g., pineal cysts) and possible demyelinating diseases [40]. Recent studies confirmed that neuroradiological abnormalities are frequent in patients with psychosis, with prevalence rates ranging from 11.1% to 15.3%, but remained mixed in their recommendation for clinical care [36,41,42]. Sommer and colleagues observed that the rate of clinically relevant abnormalities was not higher in patients than in controls and none of the radiological findings was causally related to organic psychosis [41].…”
Section: The Role Of Mri In the Diagnostic Workup Of Schizophreniamentioning
confidence: 52%
“…In this report among the most commonly observed abnormalities were vascular lesions and infarcts, localised (e.g., hippocampal) or general atrophy, benign structurers (e.g., pineal cysts) and possible demyelinating diseases [40]. Recent studies confirmed that neuroradiological abnormalities are frequent in patients with psychosis, with prevalence rates ranging from 11.1% to 15.3%, but remained mixed in their recommendation for clinical care [36,41,42]. Sommer and colleagues observed that the rate of clinically relevant abnormalities was not higher in patients than in controls and none of the radiological findings was causally related to organic psychosis [41].…”
Section: The Role Of Mri In the Diagnostic Workup Of Schizophreniamentioning
confidence: 52%
“…Past studies 2 , 3 have looked at the percentage of scans that yield a result of clinical significance and demonstrated little difference in rates of abnormal findings compared with normal controls 4 . In Beyer et al ’s study, 1 they demonstrate that the higher rates of scan abnormalities are seen in older populations. Paradoxically, while these (and other) findings suggest that brain imaging is most likely to be of clinical benefit in older patients, clinical guidelines for imaging in psychiatry predominantly refer to the first-episode psychosis population.…”
Section: Use Of Brain Imaging In First-episode Psychosismentioning
confidence: 99%
“…The population study from Beyer and colleagues 1 examines a cohort of psychiatric patients referred for brain scanning for a range of clinical indications. The study demonstrates a much higher frequency of relevant pathology (31.8%) than previously shown in screening studies.…”
Section: Findings In Beyer Et Al ’S Population Stumentioning
confidence: 99%
“…One study of 2,922 psychiatric patients at a single site showed that 31.8% had “relevant pathology” identified on imaging, with a greater chance of pathology seen in patients with dementia, head trauma, or older age. 85 “Relevant pathology” in this study, however, did not necessarily mean actionable findings—white matter hyperintensities and similar findings were included in the “hit rate” due to their potential relevance for psychiatric pathology, despite the chance that it would not change patient management. Indeed, other studies of imaging in first-episode psychosis or schizophrenia patients show significant rates of incidental findings (16–31%) but only a small percentage of those required additional medical referral or attention (2.3–10.3%).…”
Section: Laboratory and Diagnostic Testingmentioning
confidence: 99%